Synovial hemangioma localized in the knee joint and diagnosed in adulthood: MRI findings and surgical treatment: Synovial hemangioma: MRI and surgery - Akay , Emrah; Erdem , Fatih; Yanık , Bahar; Atik , Aziz; Bülbül , Erdoğan; Demirpolat , Gülen (Journal of Surgery and Medicine, 2024)
Synovial hemangioma is a rare vascular issue that can lead to persistent knee swelling and bleeding within the joint. It is typically seen in children and young adults but can also affect those in older age groups. Because the symptoms and x-ray results are not specific, it is often diagnosed late. Magnetic Resonance Imaging (MRI) is the best process for identifying and understanding the characteristics of synovial hemangioma. The recommended treatments are surgical removal and partial synovectomy, both of which offer good outcomes and minimal chance of recurrence. We discuss a case of a 48-year-old man with synovial hemangioma in the knee joint. His symptoms included swelling, pain, and restricted movement. His medical history included regular drainage of persistent knee swelling. An MRI highlighted typical features of synovial hemangioma, such as enlarged veins, looped or linear patterns, and greater visibility under gadolinium. He underwent a successful open surgery with partial synovectomy and mass removal. The pathology report confirmed the diagnosis of synovial hemangioma. Post-surgery, the patient had no complications and showed significant symptom reduction and better movement range 6 months later.